Magazin 6 : Jahresbericht 2001 : Salzburger Kunstverein Salzburg. - Amanshauser, Hildegund; Buergel, Roger M.; Faber, Monika; Gillick, Liam; Hofmann, Severin; Huck, Brigitte; Höllbacher, Roman; Kosak, Annette; Lienbacher, Ulrike; Moises, David; Morak, Franz; Phelps, Andrew; et al. (Salzburg : Salzburger Kunstverein, 2002)
Babias, Marius ; Doig, Peter ; Gerstacker, Ludwig ; Gillick, Liam ; Haas, Peter ; Iglar, Rainer ; Klapf, Udo ; Kuss, Kai ; Meyer, Anna ; Milroy, Lisa ; Nussbaumer, Günther ; Schmidt-Gleim, Meike ; Trauttmansdorff, Octavian ; Wagner, Silke ; Webb, Gary ; Wurm, Erwin ; Ziegler, Johannes ; Kosak, Annette ; Deutschbauer, Julius ; Spring, Gerhard ; Kabakov, Ilya ; Blaisse, Maria ; Windheim, Dorothee von ; Sieverding, Katharina
biog. p. 98-101
Duits & Engels
boek